Stock Market Prediction Using Analytic Hierarchy Process and Support Vector Machine - Saeed, Vaman Ashqi (Eastern Mediterranean University EMU - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
Prediction of the stock market behavior has been a research topic for decades. Because it is a challenging subject both in terms of the choice of the prediction model and in terms of constructing the set of features that model will use for forecasting. In this thesis, a novel feature ranking and feature selection approach incorporation with weighted kernel least squares support vector machines (LS-SVMs) were used. We introduce the analytic hierarchy process (AHP) into the stock market and then evaluate criteria which provide the prediction model with relevant knowledge of the underlying processes of the studied stock market. The feature weights obtained by the AHP method are applied for feature ranking and selection and used with the LS-SVMs through a weighted kernel. The experimental results specify that the new model outperforms the benchmark models. Furthermore, the set of feature weights obtained by the new approach can also independently be incorporated into other kernel-based learners. Keywords: stock market prediction, analytic hierarchy process, support vector machine, least squares support vector machines, weighted kernel.

ÖZ: Borsa davranışının tahmini çeyrek yüzyıl boyunca bir araştırma konusu olmuştur. Çünkü, tahmin modelinin seçimi ve modelin kullanacağı özellikler kümesimin inşası açılarından borsa davranışının tahmini iddialı bir konudur. Bu tezde, yeni bir özellik sıralama ve özellik seçme yöntemi, ağırlılı çekirdek en küçük kareler destek vektör makineleri (LS-SVM) beraberinde kullanılmıştır. Analitik hiyerarşi süreci (AHP) yöntemini borsa özellik seçimi için kullandık ve kullanılan borsa verileri için ilgili bilgiye dayanan tahmin modeli için kriterleri değerlendirdik. AHP ile elde edilen özellik ağırlıkları LS-SVM’in ağırlıklı çekirdek yaklaşımı aracılığıyla özellik sıralama ve seçimi için kullanıldı. Deneysel sonuçlar kullanılan modelin ölçüt modellerden daha başarılı olduğunu göstermiştir. Buna ek olarak, yeni yöntemle elde edilen özellik ağrılıkları başka çekirdek tabanlı sistemlere bağımsız olarak eklenebilir. Anahtar kelimeler: Borsa tahmini, analitik hiyerarşi süreç, destek vector makineleri, en küçük kareler destek vector makineleri, ağırlıklı çekirdek.
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2017. Supervisor: Assist. Prof. Dr. Adnan Acan.
Keywords: Computer Engineering; Machine learning; Computational intelligence-Artificial intelligence; stock market prediction; analytic hierarchy process; support vector machine; least squares support vector machines; weighted kernel